2021
DOI: 10.1002/acr2.11305
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Atorvastatin on T‐Cell Activation and Apoptosis in Systemic Lupus Erythematosus and Novel Simulated Interactions With C‐Reactive Protein and Interleukin 6

Abstract: Objective We study activation of T helper 17 (Th17) and regulatory T (Treg) cells and induction of apoptosis in cells from patients with systemic lupus erythematosus (SLE) compared with controls and effects of atorvastatin and its simulated interactions with other compounds. Methods Mononuclear cells from 10 patients with SLE and 10 controls were cultured in conditions that induce Th17 and/or Treg cell polarization and/or apoptosis and were studied by FACScan. Gene expression was determined by quantitative rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 48 publications
(62 reference statements)
0
6
0
Order By: Relevance
“…Most scholars emphasize the importance of CD4+ T cell in the development of AIH disease. IL‐17A is mainly produced by the pro‐inflammatory Th17 cells, which are closely associated with the pathogenesis of autoimmune disorders, such as AIH, [ 35 ] systemic lupus erythematosus, [ 36 ] and multiple sclerosis. [ 37 ] Pathogenic Th17 cells have been functionally defined according to their capacity to induce severe disease in models of autoimmunity.…”
Section: Discussionmentioning
confidence: 99%
“…Most scholars emphasize the importance of CD4+ T cell in the development of AIH disease. IL‐17A is mainly produced by the pro‐inflammatory Th17 cells, which are closely associated with the pathogenesis of autoimmune disorders, such as AIH, [ 35 ] systemic lupus erythematosus, [ 36 ] and multiple sclerosis. [ 37 ] Pathogenic Th17 cells have been functionally defined according to their capacity to induce severe disease in models of autoimmunity.…”
Section: Discussionmentioning
confidence: 99%
“…The powerful proinflammatory activity of Th17 cells may lead to many pathological features of SLE, such as induction of vascular inflammation, leukocyte recruitment, B cell activation, and the production of autoantibodies. 27 A large number of studies have shown that the number of Th17 cells and IL‐17A level in the peripheral blood of SLE patients have increased, and the upregulation of Th17 cells has also been found in the skin lesions, lungs, and kidneys of these patients. 28 It has been reported that Th17 cells may be involved in the abnormal immune function of autoimmune diseases such as SLE in recent years, but the specific mechanism of their role in SLE is still not fully understood.…”
Section: Discussionmentioning
confidence: 99%
“…Th17 cells are a proinflammatory subgroup of Th cells and play a crucial role in the pathogenesis of autoimmune diseases. The powerful proinflammatory activity of Th17 cells may lead to many pathological features of SLE, such as induction of vascular inflammation, leukocyte recruitment, B cell activation, and the production of autoantibodies 27 . A large number of studies have shown that the number of Th17 cells and IL‐17A level in the peripheral blood of SLE patients have increased, and the upregulation of Th17 cells has also been found in the skin lesions, lungs, and kidneys of these patients 28 .…”
Section: Discussionmentioning
confidence: 99%
“…Anti-MDA IgG, IgG1, and IgG2 levels were measured by ELISA in essentially the same way as stated 9 12 . To ensure consistency between plates, Sigma's pooled serum was utilized.…”
Section: Methodsmentioning
confidence: 99%